2013
DOI: 10.1117/1.jbo.18.5.056014
|View full text |Cite
|
Sign up to set email alerts
|

Lower body kinematics evaluation based on a multidirectional four-dimensional structured light measurement

Abstract: We report on a structured light-scanning system, the OGX|4DSCANNER, capable of capturing the surface of a human body with 2 mm spatial resolution at a 60 Hz frame-rate. The performance of modeling the human lower body dynamics is evaluated by comparing the system with the current gold standard, i.e., the VICON system. The VICON system relies on the application of reflective markers on a person's body and tracking their positions in three-dimensional space using multiple cameras [optical motion capture (OMC)]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…Some existing spatially encoded structuredlight methods rely on binary pseudo-random dots but either have relatively low frame rate and accuracy (Saberioon and Cisar, 2016;Sarbolandi et al, 2015) or require manual digitizing of numerous points per frame (Wolf and Konrath, 2015;Zhang et al, 2008). Other existing spatial methods use grayscale patterns which cannot be projected at high frame rates (Guan et al, 2003;Lenar et al, 2013;Sagawa et al, 2012;Su and Liu, 2006). Because we found that no existing system can automatically measure dynamic shape changes at sufficiently high speeds, we developed a custom method.…”
Section: Introductionmentioning
confidence: 99%
“…Some existing spatially encoded structuredlight methods rely on binary pseudo-random dots but either have relatively low frame rate and accuracy (Saberioon and Cisar, 2016;Sarbolandi et al, 2015) or require manual digitizing of numerous points per frame (Wolf and Konrath, 2015;Zhang et al, 2008). Other existing spatial methods use grayscale patterns which cannot be projected at high frame rates (Guan et al, 2003;Lenar et al, 2013;Sagawa et al, 2012;Su and Liu, 2006). Because we found that no existing system can automatically measure dynamic shape changes at sufficiently high speeds, we developed a custom method.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method must be rejected in this case due to the need for frequent measurements of children. Also, noninvasive photogrammetric methods can be used in other areas, mainly related to the faulty posture evaluation, the effect of treatment and progress in patient's rehabilitation [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…Contactless three-dimensional (3D) measurements are currently used widely, not only in engineering (reverse engineering, 3D printer technology, rapid prototyping, and quality control) [2] but also in medicine [3,4] (as measurements aiding rehabilitation, prosthetic appliance, and skeletal spine curvature assessment), in crime scene documentation [4], works of art documentation [4,5], and many other domains [6,7]. 3D scanning is currently performed using one of the following techniques [8]: laser triangulation, beam transit time, photogrammetry, or structuredlight scanning.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of using a structured-light scanner include relatively fast and contactless field measurement (multiple points in a single measurement) [4], automatic measurement process [5], fully automatic result processing [10], and high resolution (up to 10; 000 points∕mm 2 ) [5]. This measurement method also allows us to perform 3D measurements on moving objects (fourdimensional measurements) [3]. However, the method also presents some disadvantages.…”
Section: Introductionmentioning
confidence: 99%